Axial coil accelerator of plasma ring in the atmospheric pressure air - Korytchenko, K.V.; Bolyukh, V.F.; Rezinkin, O.L.; Burjakovskij, S.G.; Mesenko, O.P. (Вопросы атомной науки и техники, 2019)
An axial coil accelerator for acceleration of plasma formation having intrinsic magnetic field in the atmosphere is designed. A problem of a round plasma formation in the atmospheric pressure air is solved by electrical wire explo-sion where an initial form of an exploding wire corresponded to a ring. A vortex current into the created plasma ring is inducted by the coil accelerator to generate intrinsic magnetic field of the plasma formation. This process is syn-chronized with reduction in the magnetic coupling between the plasma formation and the accelerator coil during the acceleration.